2017
DOI: 10.1089/mdr.2016.0196
|View full text |Cite
|
Sign up to set email alerts
|

From Breast Cancer to Antimicrobial: Combating Extremely Resistant Gram-Negative “Superbugs” Using Novel Combinations of Polymyxin B with Selective Estrogen Receptor Modulators

Abstract: Novel therapeutic approaches are urgently needed to combat nosocomial infections caused by extremely drug-resistant (XDR) "superbugs." This study aimed to investigate the synergistic antibacterial activity of polymyxin B in combination with selective estrogen receptor modulators (SERMs) against problematic Gram-negative pathogens. In vitro synergistic antibacterial activity of polymyxin B and the SERMs tamoxifen, raloxifene, and toremifene was assessed using the microdilution checkerboard and static time-kill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 51 publications
2
42
0
Order By: Relevance
“…Indeed, in vitro tests combining PB and the carbapenem tigecycline using a hollow-fiber infection model have shown a bactericidal effect against CRE while suppressing the emergence of PB resistance 76 . Also, a combination of PB with a non-antibiotic drug like selective estrogen receptor modulators (SERMs) demonstrated excellent antibacterial killing kinetics against polymyxin-resistant P. aeruginosa, A. baumannii , and K. pneumoniae 77 . Given the benefit of polymyxin combination therapy, future studies could be performed to validate the activity of other polymyxin-based combinations, such as those described hereinafter.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in vitro tests combining PB and the carbapenem tigecycline using a hollow-fiber infection model have shown a bactericidal effect against CRE while suppressing the emergence of PB resistance 76 . Also, a combination of PB with a non-antibiotic drug like selective estrogen receptor modulators (SERMs) demonstrated excellent antibacterial killing kinetics against polymyxin-resistant P. aeruginosa, A. baumannii , and K. pneumoniae 77 . Given the benefit of polymyxin combination therapy, future studies could be performed to validate the activity of other polymyxin-based combinations, such as those described hereinafter.…”
Section: Resultsmentioning
confidence: 99%
“…Confocal imaging. Confocal imaging was performed to quantify the signal from cytosolic GFP; as described previously (55,56), damage to the outer membrane can cause an extensive loss of GFP and thus decreased fluorescence intensity from cytosolic GFP. In brief, bacterial cells were grown on chamber slides and treated for 2 h with monotherapies and combinations of imipenem (4 mg/liter) and tobramycin (16 mg/liter and 32 mg/liter) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the combination of an antibiotic (including polymyxins) and non-antibiotic drug has emerged as a potentially valuable and cost-effective approach to improve the clinical efficacy of currently available antibiotics against problematic MDR bacterial pathogens ( Ejim et al, 2011 ; Hussein et al, 2016 ; Schneider et al, 2016 , 2017 ). In a recent study, we demonstrated that the combination of clinically achievable concentrations of polymyxin B (2 mg/L) and the antineoplastic agent mitotane (4 mg/L) provided enhanced antimicrobial activity against MDR as well as polymyxin-resistant A. baumannii ( Tran et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%